2012
DOI: 10.1111/j.1751-2980.2012.00602.x
|View full text |Cite
|
Sign up to set email alerts
|

IRGM gene polymorphisms and risk of gastric cancer

Abstract: IRGM rs4958847 polymorphism influences susceptibility to gastric cancer, mainly for the intestinal type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…To date, only one study has addressed the association between this polymorphism and GC. In agreement with our findings, Burada et al [19], analyzing 102 GC patients, 52 chronic gastritis patients and 351 healthy controls from Romania, found IRGM rs4958847 to significantly decrease the risk of GC in this Caucasian population (OR: 0.58, 95% CI: 0.35-0.97, p-value: .038). Interestingly, similar to ATG16L1 rs2241880, there have been attempts to associate IRGM rs4958847 with CD pathogenesis.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…To date, only one study has addressed the association between this polymorphism and GC. In agreement with our findings, Burada et al [19], analyzing 102 GC patients, 52 chronic gastritis patients and 351 healthy controls from Romania, found IRGM rs4958847 to significantly decrease the risk of GC in this Caucasian population (OR: 0.58, 95% CI: 0.35-0.97, p-value: .038). Interestingly, similar to ATG16L1 rs2241880, there have been attempts to associate IRGM rs4958847 with CD pathogenesis.…”
supporting
confidence: 93%
“…In addition, IFN-c has been shown to inhibit gastric carcinogenesis by inducing epithelial cell autophagy and T-cell apoptosis in a murine model [18]. Interestingly, investigation of the association between IRGM polymorphisms (rs4958847 and rs13361189) and GC in a Caucasian population by Burada et al [19] has shown IRGM rs4958847 to decrease the risk of GC in these individuals. IRGM is located at chromosome 5q33.1 and encodes the immunity-related GTPase family M protein (IRGM), an IFN-inducible GTPase that is involved in autophagic vacuole formation.…”
mentioning
confidence: 99%
“…79 IRGM null mice are extremely susceptible to bacterial infection 80 and mutations in IRGM are linked to Helicobacter Pylori infection and gastric inflammation, which may ultimately lead to gastric cancer. 81 Polymorphism in the IRGM gene has also been linked to Chron's disease, which is often the cause of colorectal cancer. 80 IRGM is linked to apoptosis and autophagy, though its exact mechanism or role in these processes is not known.…”
Section: Autophagymentioning
confidence: 99%
“…In African American populations one CD-related polymorphism was associated positively with TB suggesting a possible link between CD and an infectious etiology. Irgm polymorphism is possibly also a risk factor for gastric cancer (Burada et al, 2012). Although deregulation of autophagy is well established to be associated with cancer (White, 2012), a role for IRGM in these diseases has to be further determined.…”
Section: Irgm Variants In Human Pathologies and Viral Infectionsmentioning
confidence: 99%